0

Equations are not displayed correctly when using

\documentclass[final,5p,times,twocolumn]{elsarticle}

while they are correctly displayed with

\documentclass[preprint,12pt,authoryear]{elsarticle}

closed as unclear what you're asking by Paul Gessler, user13907, user31729, cfr, barbara beeton Jan 2 '15 at 16:06

Please clarify your specific problem or add additional details to highlight exactly what you need. As it's currently written, it’s hard to tell exactly what you're asking. See the How to Ask page for help clarifying this question. If this question can be reworded to fit the rules in the help center, please edit the question.

  • 3
    Welcome to TeX.SX! Your question is quite unclear. Please help us to help you and add a minimal working example (MWE) that illustrates your problem. It will be much easier for us to reproduce your situation and find out what the issue is when we see compilable code, starting with \documentclass{...} and ending with \end{document}. – user31729 Sep 4 '14 at 10:25
  • 2
    Telling us merely that "equations are not displayed correctly" -- while not telling us how they're being typeset right now and how you want them to be typeset -- virtually guarantees that no answer can possibly be provided. Please post some sample LateX code with a couple of equations that you're looking to get typeset correctly. – Mico Sep 4 '14 at 11:32
1
\documentclass[final,5p,times,twocolumn]{elsarticle}

This is sufficient. However one column can contain only 29 lines and not more than that. In the first column you must have some text and it can follow required equations. Otherwise the equation moves to second column of the first page.The option 5p is used for having twocolumns in a page. It is called model 5 + journals.Please refer to elsdoc.pdf file.

code:

\documentclass[preprint,12pt,authoryear,[5p,times,twocolumn,finalprint]{elsarticle}
\usepackage{amsmath}
\begin{document}

\section{some text}
Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext Sometext sometext Sometext sometext Sometext sometext sometext Sometext sometext  Sometext sometext Sometext \\
\begin{align*}
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
\end{align*}
\begin{align*}
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
\end{align*}
\begin{align*}
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
\end{align*}
\begin{align*}
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
(a+b)^2 &= a^2+2ab+b^2\\
(a-b)^2 &= a^2-2ab+b^2\\
\end{align*}
\end{document}

output:

elsarticleclass

  • 1
    You seem to have some copy/paste errors: finalprint is not a valid elsarticle option, and there is an extra [, causing option 5p to not be recognized correctly. – Paul Gessler Sep 4 '14 at 12:52
  • @murugan: Do you mean this answer? ;-) – user31729 Sep 4 '14 at 13:54

Not the answer you're looking for? Browse other questions tagged or ask your own question.